Efektivitas Pemberian Kompres Dingin dalam Mengurangi Rasa Nyeri saat Pemasangan Infus pada Anak di IGD RSUD Temanggung - Muhammad Nur Anifan; Azizah Khoiriyati; Widayat Priyo Krisyanto (Sci-tech Journal, 2025)
Intravenous therapy is a type of therapy that is often given to children who are being treated in the hospital, especially in the intensive care unit. This therapy aims to replace lost fluids, correct electrolyte imbalances, perform blood transfusions, or administer medications. The method used is a case study on pediatric patients who underwent intravenous line installation with the main complaint of dehydration/lack of fluids. Intervention is carried out by administering a cool pack for 5-10 minutes with a cool pack temperature <10 in the area where the intravenous line will be installed. The results showed that in the first patient after the intervention of giving a cool pack with pre-installation with a Pulse result of 128x/minute, Visual Analogue Scale (VAS) value: 3. During installation, the results of the Pulse were 126x/minute, Visual Analogue Scale (VAS): 3. Post-installation, the results of the Pulse were: 120x/minute, Visual Analogue Scale (VAS): 2. In the second patient, the results of pre-installation were a Pulse result of 98x/minute, Visual Analogue Scale (VAS): 2. During intravenous installation, the results of the Pulse were 95x/minute, Visual Analogue Scale (VAS): 1. Post-installation, the results of the Pulse were: 91x/minute, Visual Analogue Scale (VAS): 1. Thus, cool pack therapy can reduce pain when intravenous lines are installed in children.